Analisis Implementasi Sistem Informasi Pemasaran di PT.GMM Surabaya - Diah Anggreini (PUTRA JAWA PUBLISHER, 2023)
The purpose of this article review or paper is to analyze the implementation of the marketing information system at PT GMM and identify the obstacles faced by the company in adopting the technology. In addition, this research aims to propose policies that can improve the effectiveness of marketing information systems and help companies achieve better goals. This research uses a literature approach and direct observation in analyzing the implementation of marketing information systems at PT GMM. The literature approach involves a review of relevant articles, papers, and other sources to understand the concepts and benefits of marketing information systems. Direct observation was conducted to observe the existing marketing practices and processes at PT GMM as well as identify the obstacles that may be faced. From this research, it has been identified that PT GMM faces challenges in the development and use of marketing information systems. The implementation of a marketing system that is still done manually causes delays in delivering information to consumers and sub-optimal product sales. To overcome this problem, this research proposes expanding the scope of marketing information systems and changing company behavior. Cooperation between company members and a deeper understanding of marketing information systems are needed to achieve better company goals.